Legal and Political Dynamics in the Village Head Election Dispute: A Socio-Legal Study of Parigi Village, Wajo Regency, Indonesia - Aminah Aminah; Muhammad Sabir; Aksah; Sunardi Purwanda; Kairuddin (DIKTUM: Jurnal Syariah dan Hukum, 2026)
Background: Village head elections (Pilkades) represent the most direct form of local democracy in Indonesia, where legal frameworks and political practices intersect to shape leadership legitimacy. Purpose: This study examines the legal and political dynamics underlying the Pilkades dispute in Parigi Village, Takkalala District, Wajo Regency, South Sulawesi, focusing on how legal mechanisms interact with local political power. Methods: Employing a qualitative socio-legal case study approach, data were collected from February to July 2024 through interviews, participatory observation, and document analysis involving election officials, candidates, legal practitioners, and community figures. Originality: This research contributes to the understanding of how law and politics are interwoven in decentralized democracies, emphasizing the need for impartial legal mechanisms and stronger community-based oversight to safeguard substantive village democracy .